Stunting policy convergence model in South Buton Regency - La Ode Syaiful Islamy Hisanuddin; Rininta Andriani; La Ode Farid Akhyar Hisanuddin (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
Stunting is not only related to health problems, but it is related to various other conditions that do not directly affect health, such as low productivity of human resources. The right policy implementation model will greatly assist in preventing stunting in society. This study aimed to model the convergence of local government policies in stunting prevention efforts by paying attention to organizational and inter-organizational behavior, lower control behavior, and target group behaviour. The study used a qualitative design with a phenomenological approach. The data were collected through in-depth interviews with 14 informants, while the secondary data came from the relevant regional apparatus organizations data. Then it was analyzed in several stages, namely the stage of data collection, data reduction, data presentation and drawing conclusions. The results of this study were that behaviour and between organizations form a commitment to contribute to stunting prevention, then at the behavioural level the organization really understood the role and function in carrying out stunting prevention and control programs, and the behaviour of the target group showed different responses positively and negatively. So that, it could be concluded consistency of policy implementers must determine shared commitments and common goals in stunting prevention.